2003
DOI: 10.3354/meps252239
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of pelagic larvae of coral-reef fishes in the ocean

Abstract: During the day, we used settlement-stage reef-fish larvae from light-traps to study in situ orientation, 100 to 1000 m from coral reefs in water 10 to 40 m deep, at Lizard Island, Great Barrier Reef. Seven species were observed off leeward Lizard Island, and 4 species off the windward side. All but 1 species swam faster than average ambient currents. Depending on area, time, and species, 80 to 100% of larvae swam directionally. Two species of butterflyfishes Chaetodon plebeius and Chaetodon aureofasciatus swam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 39 publications
4
105
1
2
Order By: Relevance
“…Irrespective of the actual settlement cues, it appears that juvenile butterflyfishes do discriminate among reef habitats. Larval butterflyfishes are very capable swimmers (Stobutzki and Bellwood 1997;Fisher 2005), and have welldeveloped sensory abilities to select suitable habitats (Leis and Carson-Ewart 2003). It is clear, however, that coral-feeding butterflyfishes are not restricted to only the most optimal habitats.…”
Section: Aureofasciatus C Baronessa C Citrinellus C Lunulatus mentioning
confidence: 99%
“…Irrespective of the actual settlement cues, it appears that juvenile butterflyfishes do discriminate among reef habitats. Larval butterflyfishes are very capable swimmers (Stobutzki and Bellwood 1997;Fisher 2005), and have welldeveloped sensory abilities to select suitable habitats (Leis and Carson-Ewart 2003). It is clear, however, that coral-feeding butterflyfishes are not restricted to only the most optimal habitats.…”
Section: Aureofasciatus C Baronessa C Citrinellus C Lunulatus mentioning
confidence: 99%
“…To enter an estuary, larvae may rely on passive transport (Jenkins et al 1997(Jenkins et al , 1999 or some form of active behaviour, such as selective tidal stream transport (Forward et al 1998(Forward et al , 1999 or active swimming (Trnski 2002, Leis & Carson-Ewart 2003. Once in the estuary, high levels of swimming performance may be required both to prevent larvae from being advected out of the estuary and to find and settle in a suitable habitat (Montgomery et al 2001).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Mouritsen et al (2013) suggested that the response evolved to counteract the prevailing NNW current. It was demonstrated that the O. doederleini larvae were navigating using a sun compass mechanism (Mouritsen et al, 2013) and sun compass orientation has also been documented in other coral reef fish species (e.g., Leis and Carson-Ewart, 2003;Berenshtein et al, 2014). Bottesch et al (2016) demonstrated that newly settled O. doederleini at OTI can also orient their swimming to the SE at night via a magnetic compass mechanism.…”
Section: Biophysical Modelingmentioning
confidence: 99%
“…The larvae of many fish species can maintain swim speeds that exceed local mean current speeds for extended periods of time, they can, therefore, influence their dispersal trajectories (Fisher, 2005;Leis, 2006). They can also orient to reefs using a variety of senses including a sun compass (e.g., Leis and Carson-Ewart, 2003;Mouritsen et al, 2013) and a magnetic compass (e.g., Bottesch et al, 2016) for long distance orientation, and hearing (e.g., Mann et al, 2007;Wright et al, 2010) and chemotaxis (e.g., Gerlach et al, 2007;Dixson et al, 2008;Paris et al, 2013) when they are closer to reefs. The exceptional swimming and orientation abilities of reef fish larvae, in combination with hydrodynamic retention mechanisms near reefs, may prevent the expatriation of some larvae away from natal reefs (Almany et al, 2007;Andutta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%